Zinc and Iron Homeostasis: Target-Based Drug Screening as New Route for Antifungal Drug Development - Simm, Claudia; May, Robin C. (Frontiers in Cellular and Infection Microbiology, 2019)
The incidence of fungal diseases is on the rise and the number of fatalities is still unacceptably high. While advances into antifungal drug development have been made there remains an urgent need to develop novel antifungal agents targeting as-yet unexploited pathways, such as metal ion homeostasis. Here we report such an approach by developing a metal sensor screen in the fatal human fungal pathogen Candida albicans. Using this reporter strain, we screened a library of 1200 compounds and discovered several active compounds not previously described as chemical entities with antifungal properties. Two of these, artemisinin and pyrvinium pamoate, have been further characterised and their interference with metal homeostasis and potential as novel antifungal compounds validated. Lastly, we demonstrate that the same strain can be used to report on intracellular conditions within host phagocytes, paving the way towards the development of novel screening platforms that could identify compounds with the potential to perturb ion homeostasis of the pathogen specifically within host cells.